2014
DOI: 10.1111/nph.13043
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific genetic diversity and composition modify species‐level diversity–productivity relationships

Abstract: SummaryBiodiversity regulates ecosystem functions such as productivity, and experimental studies of species mixtures have revealed selection and complementarity effects driving these responses. However, the impacts of intraspecific genotypic diversity in these studies are unknown, despite it forming a substantial part of the biodiversity.In a glasshouse experiment we constructed plant communities with different levels of barley (Hordeum vulgare) genotype and weed species diversity and assessed their relative b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 46 publications
(83 reference statements)
4
66
0
1
Order By: Relevance
“…Facilitative plant–plant interactions are “positive, non-trophic interactions that occur between physiologically independent plants and that are mediated through changes in the abiotic environment or through other organisms” (Brooker et al, 2008). It is widely recognized and demonstrated that heterogeneous plant communities produce more total biomass than monocultures (Newton et al, 2009; Schöb et al, 2015). The interaction of two or more crop species growing together and co-existing for a time can result in more efficient resource use through niche differentiation and complementarity.…”
Section: Plant–plant and Plant–pathogen Interactions In Mixed Plant Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Facilitative plant–plant interactions are “positive, non-trophic interactions that occur between physiologically independent plants and that are mediated through changes in the abiotic environment or through other organisms” (Brooker et al, 2008). It is widely recognized and demonstrated that heterogeneous plant communities produce more total biomass than monocultures (Newton et al, 2009; Schöb et al, 2015). The interaction of two or more crop species growing together and co-existing for a time can result in more efficient resource use through niche differentiation and complementarity.…”
Section: Plant–plant and Plant–pathogen Interactions In Mixed Plant Pmentioning
confidence: 99%
“…With respect to disease this may be critically-important as disease epidemics are a constant threat in genetically uniform crops (Finckh et al, 2000), but in climax ecosystems they are the exception. Increasing the genetic diversity within cropping systems through the use of variety or species mixtures offers a number of potential advantages not only in terms of restricting disease development, but also increasing yield stability and resilience to abiotic stress and delivering other ecosystem services including greater biodiversity (Schöb et al, 2015). Plant-plant interactions are more complex in genetically diverse populations and may involve replacement, facilitation and niche complementarity effects (Brooker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is reason to believe that selection pressures may be particularly high in constructed ecosystems, due to relatively homogeneous conditions and high levels of ecological novelty, and other features such as isolation and small population sizes can enhance drift effects, much like in natural islands (Ewel et al, 2013), leading to rapid evolution. The growing emphasis on evolutionary processes that shape ecosystem functioning (Lipowsky et al, 2011;Srivastava et al, 2012;Schöb et al, 2015) also warrants attention given the importance of ecosystem service provisioning inherent to constructed ecosystems. Evolution in these novel environments may have produced location-specific genotypes, for example, green roofs in Berlin have been present for over 100 years (Köhler and Poll, 2010), more than enough time for genetic divergence between plant populations.…”
Section: Crucibles Of Evolution?mentioning
confidence: 99%
“…A second mechanism to explain overyielding when mixing crop varieties is complementarity effects. Schöb et al (2015) found that barley genetic diversity had positive effects on aboveground biomass and attributed the overyielding due to weak complementarity effects, without specifying the niche dimensions of the varieties that enabled this complementarity. They proposed that limited trait variation associated within barley varieties is responsible for the complementarity effects in diversity-productivity studies.…”
Section: Amf Functioning In Plant-plant Interactionsmentioning
confidence: 99%
“…However, intraspecific variability could also be a cause for overyielding. Relatively few studies to that effect have been published and these were recently summarized Brooker et al 2016;Schöb et al 2015). In mixtures of susceptible and resistant blast disease rice varieties, the disease incidence in the susceptible variety was reduced compared to the sole variety, due to pathogen dilution, resulting in overyielding (Garrett and Mundt 1999;Zhu et al 2000).…”
Section: Introductionmentioning
confidence: 99%